Micro-scale mining for sustainable regional development: Exergetic analysis of a case in Guerrero, Mexico - Real-Cornejo, Anabel; Maldonado-Astudillo, Rayma Ireri; Plascencia, Gabriel (Journal of the University of Zulia, 2022)
Micro-scale or gambusina mining represents an opportunity for the social and economic development of some rural communities. However, the extractive nature of this activity also represents negative environmental impacts. This work seeks to generate proposals that support gambusino production under a sustainable scheme that can be applied by the gambusinos themselves. The research was quantitative, applied and descriptive in nature. The study was developed with a group of gambusinos located in the mining district of Coyuca de Catalán, Guerrero, Mexico, based on the analysis of exergy costs of gold extraction and refining operations, to discover the hidden costs that impact the activity. miner of the gambusinos. The results showed that the consumption of water and mercury are the elements that most affect the community. Finally, proposals were generated aimed at reducing economic costs and negative environmental impacts, while promoting the economic and social development of the community.